Application of School Teacher Literacy Culture in Efforts to Improve Education Quality in the Digitalization 4.0 Era - Khairani Khairani; Sonia Purba Tambak (Jurnal Dirosah Islamiyah, 2023)
In the industrial era 4.0, especially in the world of education, the teacher is an educator who is obliged to educate his students in learning skills, by: First, Educational competence, internet-based educational competence or learning of things as a basic skill. Second, Technology commercialization competence, has the competence to bring students to have a technology-based entrepreneurial attitude and student innovation work. Third, competence in globalization, a world without barriers, not stuttering about various cultures, hybrid competencies and problem solving competencies. Fourth, Competence in future strategy, the world changes easily and moves quickly, so that you have the competence to predict exactly what will happen in the future and its strategy. Fifth, the competence of the counselor, considering that in the future the child's problems are not difficulties in understanding teaching material, but are more related to psychological problems, stress due to increasingly complex and severe pressure conditions, a teacher who is able to behave is needed. as a counselor/psychologist. Why are they called teachers because some people think that all areas of the teacher must be mastered even though sometimes we cannot lie to ourselves, if we have to master all fields we may not be able to, but there is nothing wrong if these deficiencies must be covered with lifelong learning. And continue to accompany these students to continue learning and learning. Keywords: Teacher and Student Literacy Culture, Education, Digitalization age 4.0